Enhanced source memory for cheaters with higher resemblance to own-culture typical faces - Burhan, Pinar; Alici, Tevfik (Springer, 2023)
Recent evidence suggests that culture-specific face typicality has an impact on making trait judgments. Additionally, facial resemblance to one's culture-typical faces causes them to be perceived as reliable, less dangerous, and more accurately recognized. When judging persons from other cultural origins, one's own culture's face standards might shape inferences, behavior, and memory. In this study, the partners' facial resemblance to participants' culturally typical faces was manipulated using target faces, considered to be higher or lower, similar to people living in the participants' hometown. Participants were asked to invest in a company together with partners who have a higher and lower resemblance to their own-culture typical faces in a cooperation game. The results showed that facial resemblance to own-culture typical faces affected investment preferences. Partners with a higher resemblance to own-culture typical faces were more correctly distinguished in the old-new recognition memory task. The study found that partners with a higher resemblance to own-culture typical faces had a source memory advantage for cheating behaviors. These results confirmed that a higher resemblance to own-culture typical faces provide an advantage in cross-cultural interactions, allowing them to become better recognized. Additionally, enhanced source memory for cheaters with higher resemblance to own-culture typical faces may indicate a flexible cognitive system that is sensitive to information that violates social expectations.
Keywords: Source memory; Cheaters; Expectation violation; Facial resemblance; Own-culture typical faces